KEKUASAAN DAN KEDAULATAN MEMERINTAH - Muhtar Habbodin; Mohamad Firdaus (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
Power and sovereignty are interrelated in governance. The government in power has sovereignty in governing which comes from the people through a consensus (government making). Therefore, the ruling government must be responsible to the people who are then transformed into citizens (citizen making). This is practiced in a democratic government system. In contrast, the authoritarian system of government power is in the hands of the government. The position of the people is weak and marginalized in power. These two systems of government are still ongoing today. However, the most dominant and widely practiced is the power that comes from the people. Instrumentation of people's power when choosing sovereign leaders through democratic elections. The choice of a leader is largely determined by the people. This proves that the power and sovereignty of governing are in the control of the people. Therefore, power needs to be oriented to the interests of the people who are citizens, and at the same time be held accountable. The people encourage all leaders in power to be accountable and take political sides with the citizens by making the government the administrator and regulator of the benefit of the citizens.